X-(1-x)=2

Simple and best practice solution for X-(1-x)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X-(1-x)=2 equation:


Simplifying
X + -1(1 + -1x) = 2
X + (1 * -1 + -1x * -1) = 2
X + (-1 + 1x) = 2

Reorder the terms:
-1 + X + 1x = 2

Solving
-1 + X + 1x = 2

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + X + 1 + 1x = 2 + 1

Reorder the terms:
-1 + 1 + X + 1x = 2 + 1

Combine like terms: -1 + 1 = 0
0 + X + 1x = 2 + 1
X + 1x = 2 + 1

Combine like terms: 2 + 1 = 3
X + 1x = 3

Add '-1x' to each side of the equation.
X + 1x + -1x = 3 + -1x

Combine like terms: 1x + -1x = 0
X + 0 = 3 + -1x
X = 3 + -1x

Simplifying
X = 3 + -1x

See similar equations:

| -2x^2+20x-47=0 | | 5(6-7)=10 | | X+3x+2=5x+6 | | -2x^2+20x-36=0 | | -2x^2+20x-39=0 | | 2(x+5)-x=x+10 | | 4x-3=2x-1/3 | | 45=9x+9 | | (Y)+y=2 | | -10x-17=167 | | 3*x+20=5*x-4 | | 4a^5-500a^2=0 | | 68hm=km | | r^2+12r-189=0 | | 9w+1+3(w+2)= | | 8x-14=x^2+x-2 | | 3-(4x-3)=1 | | -45+m=24 | | 6n-24=9-3n-3 | | K^2+8=56 | | p(2+5p)= | | 3/2=x/11 | | 2x-35(4+5)=40 | | 2lnx-1= | | (4x-52)+(x+32)+(.5x+46)= | | x-5=5+x | | 2z+12=3-z | | 3x+5+2x-1=3x+17 | | 6a-8=3a+7 | | 7x-2x+7=2x+32 | | 8+2(8x-6)=2(4+7) | | (10x-20)+(x+52)+(.125x+59)= |

Equations solver categories